2016
DOI: 10.5539/ijbm.v11n11p196
|View full text |Cite
|
Sign up to set email alerts
|

Improving Employees Behavior through Extension in Theory of Planned Behavior: A Theoretical Perspective for SMEs

Abstract: The purpose of this paper is to review the conceptualization of the adaptation of Theory of Planned Behavior (TPB) with religious orientation in small and medium enterprises (SMEs). The underlying assumption for TPB implication in SMEs is that employee's behavioral intention at work may be modified via TPB which shall improve the employee competitiveness, which in turn increases the organizational success factors in the industry. The proposed conceptual framework is based on well-known analytical framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 128 publications
(118 reference statements)
0
14
0
2
Order By: Relevance
“…Faktor (Ajzen, 2005). Niat seseoorang ditentukan oleh behavior belief, normatif belief, dan control belief (Sulistiyani, 2016) dan (Ghouri et al, 2016). Berdasarkan teori ini, kesadaran wajib pajak berkaitan dengan behavior belief yang menjelaskan bahwa sikap individu akan memengaruhi keinginan individu dalam bertindak dengan mengetahui hasil dari tindakan yang dilakukan individu tersebut.…”
Section: Pendahuluanunclassified
“…Faktor (Ajzen, 2005). Niat seseoorang ditentukan oleh behavior belief, normatif belief, dan control belief (Sulistiyani, 2016) dan (Ghouri et al, 2016). Berdasarkan teori ini, kesadaran wajib pajak berkaitan dengan behavior belief yang menjelaskan bahwa sikap individu akan memengaruhi keinginan individu dalam bertindak dengan mengetahui hasil dari tindakan yang dilakukan individu tersebut.…”
Section: Pendahuluanunclassified
“…Religion engenders the shape of behaviour, which is strongly followed by people (Ghouri, Khan & Kareem, 2016;Ghouri et al, 2018). Previous studies that involved religiosity and work behaviour found significant relationship between the two variables (Weaver & Agle, 2002;Emmons & Paloutzian, 2003;Gibson 2005;Pargament, Magyar-Russell & Murray-Swank, 2005;Sikorska-Simmons, 2005;Ahmad Amri et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 92%
“…The fitness test of the confirmatory factor analysis model found that all fitness index values, Root Mean Square of Error Approximation (RMSEA), Goodness of Fit Index (GFI), Comparative Fit Index (CFI), and Chi Square / Degree of Freedom (Chisq/df) used demonstrate fitness has been achieved [17] , [18] , [19] , [20] , [21] , [22] . The results of the model fitness test are shown in Table 2 .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%